(NnEZR)QÆWNQNNIJ (B- Æ(NZ rÆWNÆ(B. (NsERÆQ LISTÆWOK DO (B70-(NRÆ^^Q Z DNQ NARODVENNQ SPÆWAKA Æ POETA nAZARÆQ qREM^UKA (B/s)E - (NwOZN@K(B, (Nw(B. (No(B.s ((NwOLODIMIR oKSENT)QÆJOWI^(B)s)E; (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NbALAN@K(B, (Nt(B.s ((NtARAS(B)s; (NgALQBARDA(B, (Ns(B. (Np(B.s ((NsTEPAN pETROWI^(B)s; (NdU]AK(B, (Na(B. (Nk(B.s ((NaNNA kIRIL)QÆWNA(B)s)E; (NbALAN@K(B, (Nt(B.s ((NtARAS(B)s; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2021)
(NsER)QÆQ LISTÆWOK (B"(NnEZRÆWNQNNIJ (B- Æ(NZ rÆWNÆ(B" (N^ERGOWE WIDANNQ WIDAWNICTWA (B"(NrODOWÆD(B". (NtUT WMÆ]ENO WÆR[Æ(B-(NPRISWQTI WELIKOMU UKRAÇNSXKOMU SPÆWAKOWÆ nAZARÆ@ qREM^UKU DO (B70-(NRÆ^^Q Z DNQ NARODVENNQ (B20 (NPOETÆW(B, (NTAKIH QK wÆTALÆJ dEM^ENKO(B, (NoLEKSANDR dOWBU[(B, (NsTEPAN pAN^UK(B, (NsTEPAN gALQBARDA(B, (NwOLODIMIR wOZN@K(B, (NgALINA tARAS@K TA ÆN[IH(B. s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI ZA PÆDTRIMKI AWTORÆW Æ MECENATÆWs)E
Keywords: (NqREM^UK(B, (NnAZAR)QÆJ nAZAROWI^(B,s)E -- 1951-1995 (NRR(B.s; (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E